A review on the application of various MQL base in metal cutting operation of aluminum alloys - Mokhtar, Suhaily; A. Raof, Natasha; Muhammad Khairusalleh, Nor Khairusshima; Dahnel, Aishah Najiah (The Mattingley Publishing Co., Inc., 2020)
Lubricant is an important element that acts as a cutting fluid and coolant in metal cutting processes. The function of the lubricant is to reduce the heat generated at the cutting tool-workpiece and cutting tool- chips interfaces. The heat generated at the cutting zone promotes rapid wear progression of the cutting tool which leads to high cutting force, poor surface finish and inaccurate dimensional tolerance of the component being cut. The lubricant supplied during metal cutting processes in flood machining is unfavorable as it contributes to high manufacturing cost, hazardous to machinists and contributes to environmental issues. Lubrication through Minimum Quantity Lubrication (MQL) was introduced to replace the flood cutting. MQL flow at 50ml/h to 100ml/h through the external or internal channel and sprayed towards the cutting zone. A lot of studies were conducted to observe the effect of MQL on various types of ferrous and non-ferrous metal with regards to the cutting force, surface integrity and tool wear progression during metal cutting processes. In this paper, a review of available literature on MQL applications during machining Aluminum Alloys was conducted. Factors such as MQL base and techniques, cutting parameters and cutting tools were observed to be important in the metal cutting processes. The performance, advantages and disadvantages of each study were highlighted base on the outcome of the conducted studies